Acute myeloid leukaemia presenting with ecthyma gangrenosum as the first manifestation: A case report. Issue 18 (7th May 2021) - Hadano, Yoshiro; Yoshida-Sakai, Nao; Imamura, Yutaka; Inoue, Tomohiro; Koga, Hitoshi
Abstract: Rationale: Ecthyma gangrenosum (EG) is an uncommon cutaneous infection usually associated with Pseudomonas aeruginosa bacteremia in immunocompromised patients, particularly those with underlying malignant diseases. Despite its rarity, especially in immunocompetent or nondiagnosed immunodeficiency patients, EG can present as the first manifestation of an underlying immunosuppression. Patient concerns: A 42-year-old Japanese man was admitted to our hospital with a 3-day history of a painless red macule on his right forearm and fever. Diagnoses: Blood culture on admission revealed the presence of Pseudomonas aeruginosa, whereas pus culture of the skin lesion showed Pseudomonas aeruginosa and methicillin-susceptible Staphylococcus aureus positivity. Interventions: Additional bone marrow aspirate examination and immunophenotyping were performed to confirm the diagnosis of acute promyelocytic leukaemia with PML-retinoic acid alpha receptor. Outcomes: The patient was successfully treated with a 14-day course of antibiotics, and no evidence of relapse was noted. The patient achieved complete remission after treatment for acute promyelocytic leukaemia. Lessons: It should be kept in mind that EG is an important cutaneous infection that is typically associated with P aeruginosa bacteremia and the presence of underlying immunodeficiency, such as acute leukaemia.